2005
DOI: 10.1128/jcm.43.6.2729-2735.2005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Fluconazole Resistance in a Candida parapsilosis Strain That Caused Infections in a Neonatal Intensive Care Unit

Abstract: Candida parapsilosis is an increasing cause of bloodstream infections (BSIs) in neonatal intensive care units (NICUs).During the last decades the incidence of candidemia in neonatal intensive care units (NICUs) has increased, and the most prevalent Candida species that cause candidemias have shifted over time from Candida albicans to Candida parapsilosis (12,16,23). The known risk factors for candidemia are prematurity; the use of central venous lines, intubation, parenteral nutrition, and broad-spectrum antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
124
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 36 publications
5
124
0
1
Order By: Relevance
“…Candida parapsilosis is a well-known cause of nosocomial bloodstream infections, particularly among neonates and immunocompromised patients, and it is associated with candidaemia caused by intravascular and parenteral nutrition devices (Sarvikivi et al, 2005;Almirante et al, 2006;Pfaller & Diekema, 2002;Trofa et al, 2008). C. parapsilosis groups I, II and III were recently established as distinct species, which were classified by genotyping and designated C. parapsilosis sensu stricto, C. orthopsilosis and C. metapsilosis, respectively (Tavanti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida parapsilosis is a well-known cause of nosocomial bloodstream infections, particularly among neonates and immunocompromised patients, and it is associated with candidaemia caused by intravascular and parenteral nutrition devices (Sarvikivi et al, 2005;Almirante et al, 2006;Pfaller & Diekema, 2002;Trofa et al, 2008). C. parapsilosis groups I, II and III were recently established as distinct species, which were classified by genotyping and designated C. parapsilosis sensu stricto, C. orthopsilosis and C. metapsilosis, respectively (Tavanti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the C. parapsilosis complex are normally susceptible to most antifungal compounds but previous studies reported decreased responsiveness to fluconazole (FLC) and caspofungin (CASPO) (Sarvikivi et al, 2005;Legout et al, 2006;Lockhart et al, 2008;van Asbeck et al, 2008;Gonçalves et al, 2010;Silva et al, 2009). It was also suggested that C. orthopsilosis and C. metapsilosis might be more susceptible to amphotericin B (AMB) and echinocandins than C. parapsilosis sensu stricto (Gomez-Lopez et al, 2008;van Asbeck et al, 2008;Garcia-Effron et al, 2008) and that these differences in antifungal susceptibility could affect choice of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies have demonstrated that prophylactic fluconazole decreases fungal colonization and subsequent invasive fungal infection in PT infants. [4][5][6][7][8] The duration of prophylaxis in most of these studies is from 4 to 6 weeks, starting at birth to 3 days of age. 4,5,8 The risk of invasive candidiasis persists from birth to 3 months, with the highest risk reported to be between 11 and 20 days of life.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] The duration of prophylaxis in most of these studies is from 4 to 6 weeks, starting at birth to 3 days of age. 4,5,8 The risk of invasive candidiasis persists from birth to 3 months, with the highest risk reported to be between 11 and 20 days of life. 1 The approach of prophylaxis, from 4 to 6 weeks, to all extremely low birth weight infants treats a large number of infants for a prolonged duration, some of whom may be at low risk for infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation